Influência do hormônio tireoideano t3 tópico sobre os osteócitos em defeitos ósseos críticos de calvária de ratos Wistar - Munhoz, Maira Foresti Vieira (2013)
The aim of this study was to evaluate the influence of topic thyroid hormone (T3) on the osteocytes in calvarial critical bone defects in rats. We used 30 male Wistar rats were randomly divided into three groups (n=10): control (bone defect filled with a placebo consisting of base ointment), treated group 1 (bone defect filled with T3 in ointment at a concentration of 0.03%) and group 2 treated (bone defect filled with T3 in ointment at a concentration of 3%), tested at 30 and 60 days. Critical bone defects were made in the skull 8mm animals, filled with ointment, and analyzed the periods proposed. We performed histological, morphometric and morphologic analysis of gaps and counting of osteocytes. Histologically, the group treated with T3 at 0.03% showed an acceleration of bone remodeling and turnover, within 30 days, which were observed reversal lines and osteocytes organizing themselves around the Havers channels. At 60 days, this same treatment, reversal lines are diminished. At 30 days, the control showed bone formation 672.25 ± 89.10 mm2, whereas in the group treated with 0.03% of the T3 had the highest bone formation (1640.5 ± 215.52 mm2) statistically different (p <0.05). The group treated with 3% T3 was not different from the other groups (1006 ± 302.72 mm2) (p> 0.05). At 60 days, bone formation in the control group was 81.5 ± 927 mm2, while the group treated with T3 was 0.03% 1176.25 ± 220.65 mm2 (p> 0.05). Formation of 1065 ± 13.29 mm2 Bone treatment with T3 was 3% greater than the control (p <0.05), but similar treatment with 0.03% T3 (p> 0.05). At 30 days, compared to the amount of gaps in osteocytes, the group treated with T3 at a concentration of 0.03% had the highest number of osteocytes present in the lacunae of bone formation (217.5 ± 34.64 mm2), statistically diferente (p <0.05) the number of cells observed in the control group (153.25 ± 18.73 mm2). At 60 days, the amount of gaps osteocytes observed in different treatments was not statistically different between groups (p> 0.05). At 30 days, compared to the morphology of the osteocytes, the T3-treated group showed greater activity of these cells, with extensive canals and wide network of connections. It was concluded that the ointment containing T3 at a concentration of 0.03%, assists bone healing within 30 days, providing greater bone formation. The action of the hormone caused na increase in the number and morphology of osteocytes lacunae in the same concentration and period in which there was greater bone formation.